Incidence and Epidemiology of Thoracolumbar Spine Fractures: WFNS Spine Committee Recommendations - Zileli, Mehmet; Sharif, Salman; Fornari, Maurizio (International neurourology journal, 2021)
This review aims to search the epidemiology and incidence rates of thoracolumbar spine fractures. A systematic review of the literature of the last 10 years gave 586 results with “incidence,” and 387 results with “epidemiology,” of which 39 papers were analyzed. The review results were discussed and voted in 2 consensus meetings of the WFNS (World Federation of Neurosurgical Societies) Spine Committee. Out of 39 studies, 15 studies have focused on thoracolumbar trauma, remaining 24 studies have looked at all spine trauma. Most were retrospective in nature; few were prospective and multicenter. Some studies have focused on specific injuries. The annual incidence of TL fractures is about 30/100,000 inhabitants including osteoporotic fractures. There is a trend to increase the fractures in elderly population especially in developed countries, while an increase of motor vehicle accidents in developing countries. The mortality rate among male elderly patients is relatively high. The incidence of thoracolumbar spine fractures is increasing because of low-velocity falls in the elderly population. The main reasons are falls and traffic accidents. Learning the regional differences and some special forms of trauma such as extreme sports, war, and gunshot injuries will help the prevention of the thoracolumbar spine fractures.